Digital Literacy as a Strategy for Democratic Resilience: Countering Disinformation and Reducing Self-Censorship - Dedy Helsyanto; Maria Puspitasari (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Democracy in Indonesia faces serious challenges due to increasing polarization, the weakening of freedom of expression, and the widespread dissemination of disinformation. Public distrust toward institutions, along with growing social pressure, has led to self censorship, which hinders citizen participation in public discourse. These conditions pose a threat to democratic resilience and call for effective mitigation strategies. However, there is still a gap in understanding how digital literacy can help individuals recognize disinformation and reduce self-censorship. Moreover, few studies have comprehensively explored the relationship between digital literacy and democratic resilience. This study adopts a literature review approach to examine existing research on the role of digital literacy in safeguarding democracy in the face of disinformation and self-censorship. The findings indicate that digital literacy enhances critical thinking skills, the ability to identify credible information, and supports freer public participation. Digital literacy also helps reduce self-censorship by equipping individuals to cope with social pressures and legal threats. This article analyzes the link between self-censorship and disinformation within the context of digital literacy—an area that remains underexplored. It further proposes digital literacy strategies based on policy, education, and community engagement to build collective resilience. The study offers a multi-stakeholder model as a strategic recommendation for policymakers, educators, and communities to design more adaptive digital literacy initiatives. Digital literacy is positioned as a foundational tool to build a society that is resilient to disinformation and political manipulation, while also strengthening an inclusive and participatory democracy.